2003
DOI: 10.1037/0012-1649.39.2.274
|View full text |Cite
|
Sign up to set email alerts
|

The developmental ecology of urban males' youth violence.

Abstract: Data from a longitudinal study of 294 African American and Latino adolescent boys and their caregivers living in poor urban communities were used to test a developmental-ecological model of violence. Six annual waves of data were applied to evaluate the relations between microsystem influences of parenting and peer deviance (peer violence and gang membership), macrosystem influences of community structural characteristics and neighborhood social organization, and individual involvement in violence (level and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
219
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(245 citation statements)
references
References 61 publications
(150 reference statements)
18
219
1
7
Order By: Relevance
“…Reported frequencies for each event were recoded using the scale: 0 -none, 1 -once, 2 -more than once. Consistent with previous studies and a widely accepted method within the field (e.g., Elliott, Dunford, & Huizinga, 1987;Loeber, Stouthamer-Loeber, & White, 1999;Tolan, Gorman-Smith, & Henry, 2003), we weighted the recoded frequencies for each event by legal seriousness, ranging between an index of 4 (Class A misdemeanors, such as item 1) to an index of 8 (Class 1, corresponding to serious felonies, such as items 6-8). Item 2 was weighted by an index of 5, items 3-4 were weighted by an index of 6, and item 5 was weighted by an index of 7.…”
Section: Methodssupporting
confidence: 75%
“…Reported frequencies for each event were recoded using the scale: 0 -none, 1 -once, 2 -more than once. Consistent with previous studies and a widely accepted method within the field (e.g., Elliott, Dunford, & Huizinga, 1987;Loeber, Stouthamer-Loeber, & White, 1999;Tolan, Gorman-Smith, & Henry, 2003), we weighted the recoded frequencies for each event by legal seriousness, ranging between an index of 4 (Class A misdemeanors, such as item 1) to an index of 8 (Class 1, corresponding to serious felonies, such as items 6-8). Item 2 was weighted by an index of 5, items 3-4 were weighted by an index of 6, and item 5 was weighted by an index of 7.…”
Section: Methodssupporting
confidence: 75%
“…For instance, gang involvement may lead to increased community violence exposure, or adolescents may join gangs as a consequence of exposure to such violence. Although some researchers have found that community violence exposure is an antecedent to gang involvement (Tolan, Gorman-Smith, & Henry, 2003), future studies using longitudinal designs will need to further disentangle such associations. Findings may also be limited by the validity of the self-reported measures, by the use of a convenience sample of detained adolescents in part necessitated by the need to obtain parental consent and by the possibility of response bias, although sophisticated computer technology was employed in order to reduce such occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, parents and schools may have some effect in reducing involvement in violence (Fauth, Roth, & Brooks-Gunn, 2007;Ingoldsby et al, 2012;Tolan et al, 2003). Expanded research is needed on effective interventions to reduce youth violence in this context.…”
Section: Family Environmentmentioning
confidence: 99%